Depth of field in dental photography and methods for its control - Dukić Zlatomir (Serbian Medical Society - Dental Section, Belgrade, 2014)
The emergence of photographs has been a milestone in the development of society by making life richer and more comprehensive. Dental photography as part of clinical medical photography plays a role primarily as a document, but also as a tool for educating students and continuing education of dentists. The aim of this paper is to present possible applications of traditional and digital photography in dentistry at the present stage of technological development. Dental photography requires some knowledge and equipment to obtain quality images of intraoral structures. The control of depth of field (DOF) is one of the important factors for successful dental photography. DOF can be controlled by changing relative aperture, using special lenses with decentring to achieve the effect of Scheimpflug's principle as well as the use of specialized software which uses series of images with selective focus to form a composite picture. Special significance of dental photography is documentation and ability to record maximum information in conditions that can be repeated. Standardization of conditions during recording oral cavity, adequate storage and archiving of dental photographs are also important prerequisites for quality and useful photography.